ANALISIS BEBAN PENCEMAR DAN KAPASITAS ASIMILASI DI MUARA SUNGAI TONDANO TELUK MANADO - Irman Rumengan; Haeruddin Haeruddin; Pujiono Wahyu Purnomo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
The Tondano river estuary waters is located in the Manado city, North Sulawesi Province. Receiving inputs from rural, urban, hydropower, agriculture, plantation, livestock, and industrial activities is high enough to cause a decrease in the quality of Tondano river estuary waters. The aim of this research is to analyze the pollutant load from Tondano river and the assimilation capacity of Tondano river estuary waters. The study was conducted in December 2016 - January 2017 in the waters of the Tondano river estuary. The research method refers to the approach of measuring pollution load of river estuary. Multiplication of concentration of pollution variables with river flow discharge, calculation of assimilation capacity by making a graph of the relationship between pollutant concentration and pollutant load at river estuary, which then analyzed with water quality standard value for marine life based on Decree of State Minister of Environment Number 51 of 2004. The measurement results showed that the pollution load value of BOD5 was 261,473 mg/s, nitrate (NO3-N) of 0,747 mg/s, lead (Pb) of 0,747 mg/s, and phosphate (PO4-P) of 0,311 mg/s. The pollution load variable that has passed the assimilation capacity is NO3-N, PO4-P, and Pb, while the variable that has not passed the assimilation capacity is BOD5. From the results, it can be concluded that the waters of the Tondano river estuary have been polluted by NO3-N, PO4-P, and Pb contaminants. Water pollution control of Tondano river estuary needs to be done more tightly so that the potential of coastal and marine resources remain sustainable.